Engineered Anti‐GPC3 Immunotoxin, HN3‐ABD‐T20, Produces Regression in Mouse Liver Cancer Xenografts Through Prolonged Serum Retention. Issue 5 (27th January 2020) - Fleming, Bryan D.; Urban, Daniel J.; Hall, Matthew D.; Longerich, Thomas; Greten, Tim F.; Pastan, Ira; Ho, Mitchell
Abstract : Background and Aims: Treatment of hepatocellular carcinomas using our glypican‐3 (GPC3)‐targeting human nanobody (HN3) immunotoxins causes potent tumor regression by blocking protein synthesis and down‐regulating the Wnt signaling pathway. However, immunogenicity and a short serum half‐life may limit the ability of immunotoxins to transition to the clinic. Approach and Results: To address these concerns, we engineered HN3‐based immunotoxins to contain various deimmunized Pseudomonas exotoxin (PE) domains. This included HN3‐T20, which was modified to remove T‐cell epitopes and contains a PE domain II truncation. We compared them to our previously reported B‐cell deimmunized immunotoxin (HN3‐mPE24) and our original HN3‐immunotoxin with a wild‐type PE domain (HN3‐PE38). All of our immunotoxins displayed high affinity to human GPC3, with HN3‐T20 having a KD value of 7.4 nM. HN3‐T20 retained 73% enzymatic activity when compared with the wild‐type immunotoxin in an adenosine diphosphate–ribosylation assay. Interestingly, a real‐time cell growth inhibition assay demonstrated that a single dose of HN3‐T20 at 62.5 ng/mL (1.6 nM) was capable of inhibiting nearly all cell proliferation during the 10‐day experiment. To enhance HN3‐T20's serum retention, we tested the effect of adding a streptococcal albumin‐binding domain (ABD) and a llama single‐domain antibody fragment specific for mouse and human serum albumin. For the detection of immunotoxin in mouse serum, we developed a highly sensitive enzyme‐linked immunosorbent assay and found that HN3‐ABD‐T20 had a 45‐fold higher serum half‐life than HN3‐T20 (326 minutes vs. 7.3 minutes); consequently, addition of an ABD resulted in HN3‐ABD‐T20–mediated tumor regression at 1 mg/kg. Conclusion: These data indicate that ABD‐containing deimmunized HN3‐T20 immunotoxins are high‐potency therapeutics ready to be evaluated in clinical trials for the treatment of liver cancer.